Performing motherhood in the height of the New Order era: The contestation of two women in Dua Ibu - Edi Dwi Riyanto; Yuanita Albhar (Universitas Islam Sultan Agung, 2021)
The New Order regime in Indonesia was marked with a strong and centralized power including in defining motherhood. This article is aimed at investigating how the “Ibu” or motherhood becomes a contested arena between nameless Ibu and Tante Mirah and how this arena reflects the contestation of tradition and modernity in Java in the 1980s. Using close reading technique and contextualization, an investigation is done to see how the one role is contested by the two women. The nameless Ibu represents traditions shaped by the cultural and traditional milieu in Solo, Central Java. Meanwhile Tante Mirah migrates to Jakarta and builds her new economy and life. It is evident that performing traditions has drained out Ibu’s financial resources. At the same time, Tante Mirah is successful in accumulating wealth. Consequently, Ibu goes bankrupt and lets Mirah take the son back. The novel documents the inevitable change of socially defined motherhood performed in the center of Javanese culture.